Money in their own name : the feminist voice in poverty debate in Canada, 1970-1995 - McKeen, Wendy, 1954- (Studies in comparative political economy and public policy., 2004)
In Money In Their Own Name, Wendy McKeen examines the relationship between gender and social policy in Canada from the 1970s to the 1990s. She provides a detailed historical account of the shaping of feminist politics within the field of federal child benefits programs in Canada, and explores the critical issue of why feminists' vision of the 'social individual' failed to flourish. Canadian social policy, as in most western welfare states, has established women's access to social benefits on the basis of their status as wives or mothers, not individuals in their own right. In her analysis, McKeen underscores this persistent familialism that has been written and rewritten into Canadian social policy thereby denying women's autonomy as independent claims-makers on the state. She further demonstrates the lack of contest by the women's movement toward this dependent status, and the consequent erasure of women from social policy. McKeen effectively weaves together sociological theory with substantive examples from political discourse. She uncovers overlooked aspects of Canadian social policy politics and subsequently extends our understanding of politics and political change. At the same time, by synthesizing the concepts of discourse, agency, and policy community, she offers a new analytical tool for approaching the shaping of political interests.